Vibrational Spectra of 2,4-Dimethyl-6-Hydroxy Pyrimidine - Singh, Vir; Kumar, Vipin; Yadav, M.K.; Yadav, B.S. (Asian Journal of Chemistry, 2010)
The vibrational (infrared and Raman) spectra of 2,4-dimethyl-6-hydroxy pyrimidine are reported. The assignments of fundamentals are proposed and discussed by assuming the molecule under C2v point group symmetry. Tautomeric behaviour of the compound is also discussed.